PERBEDAAN KETERAMPILAN BERPIKIR KRITIS DAN PRESTASI BELAJARDENGAN MENGGUNAKAN PENDEKATAN PEMECAHAN MASALAH PADA PEMBELAJARAN LARUTAN PENYANGGAKELAS XI IPA SMA NEGERI 1 SENTANI - Suryati, Nurmina; Siregar, Tiurlina (Jurnal Ilmu Pendidikan Indonesia, 2013)
ABSTRACT The objectives of this research are: 1. To product buffer learning approach with problem solving approach for increasing critical thinking ability and studentsâ achievement. 2. To know effectivity of problem solving approach that increase studentsâ understanding, studentsâ achievement, critical skill, ability for appiying concept in daily life and problem solving. The method of this research is experiment quasi â one group pretest-postest design âthat invoire 60 (sixty) of eleventh grade natural science student. The data got by beginning (pretest) test and end test (posttest) to know inereasing concept mastery, learning achievement, critical thinking ability and problem solving ability of students, that processed using statistic method, SPSS 16. There was significance between concept mastery and critical thinking ability in experiment class and control class observed from t counted 0,000 < t table 0,05 that means problem solving approach treatment infivence studentsâ critical thinking ability, whereas learning achievement in control class and experiment are not significance, t counted 0,581 > t table 0,05, means problem solving approach treatment are not irfivential on learning achievement. Key word : learning achievement, critical thinking ability, concept mastery and problem solving.